Creating voluntary payment programs effective program design and ranchers' willingness to conserve Florida panther habitat - Pienaar, Elizabeth F., author; Kreye, Melissa M., author; Soto, José R., author; Adams, Damian C., author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Landowner resistance to Endangered Species Act (ESA) regulations is a key challenge to endangered species protection and recovery. Payments for Ecosystem Services (PES) strategies have been promoted as an effective market-based strategy for conserving imperiled species and offsetting ESA regulatory pressure on private landowners. The U.S. Fish and Wildlife Service (USFWS) recently proposed that a mix of PES and regulatory assurances be implemented in Florida to encourage cattlemen to engage in Florida panther recovery efforts. To identify cattlemen's preferences for the proposed programs we conducted a mail-based survey employing a choice experiment typically used in marketing research (i.e., best-worst scaling). We found that the utility associated with an incentive program depends on both the type and level of incentive offered and contract features that impact personal autonomy. Our findings suggest that voluntary conservation programs are most likely to enroll politically conservative landowners if these programs (1) provide per-acre payments or tax reductions, (2) are of shorter duration, (3) are based on norms of reciprocity, and (4) do not require overly intrusive or restrictive levels of monitoring to ensure program compliance.
Creating voluntary payment programs to promote endangered wildlife recovery: effective program design and ranchers' willingness to conserve Florida panther habitat
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.